2011
DOI: 10.1016/j.postharvbio.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest application of gum arabic and essential oils for controlling anthracnose and quality of banana and papaya during cold storage

Abstract: Management of anthracnose caused by Colletotrichum spp. is the most important issue for the tropical fruit industry because of resulting financial losses. Antifungal effects of gum arabic (GA) (10%), lemongrass oil (LG) (0.05%), cinnamon oil (CM) (0.4%), and their combinations were investigated in vitro and in vivo for controlling postharvest anthracnose of banana and papaya. LG at 0.05% and 0.4% CM showed fungicidal effects against Colletotrichum musae and Colletotrichum gloeosporioides, causal organisms of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
119
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(130 citation statements)
references
References 26 publications
9
119
0
2
Order By: Relevance
“…All the coating emulsions tested under the current study significantly reduced the weight loss as compared to the controls. Similar results were observed in tomato fruits treated with gum arabic coatings (Ali et al, 2010) and papaya fruits with chitosan coating (Maqbool et al, 2011). The positive effect of chitosan coating on a storage life of fruits could due to the modifying the internal atmosphere of fruits.…”
Section: Effect Of Gum Ghatti Based Edible Coating Emulsion On Weightsupporting
confidence: 81%
“…All the coating emulsions tested under the current study significantly reduced the weight loss as compared to the controls. Similar results were observed in tomato fruits treated with gum arabic coatings (Ali et al, 2010) and papaya fruits with chitosan coating (Maqbool et al, 2011). The positive effect of chitosan coating on a storage life of fruits could due to the modifying the internal atmosphere of fruits.…”
Section: Effect Of Gum Ghatti Based Edible Coating Emulsion On Weightsupporting
confidence: 81%
“…Our findings are in accordance with Al-Juhaimi et al [45] who reported that cucumber fruit coated with 20% gum arabic solution notably maintained firmness by acting as a barrier against nutrients and water loss. In another study, Maqbool et al [29] reported that banana fruit coated with gum arabic combined with chitosan efficiently maintained higher firmness during cold storage.…”
Section: Discussionmentioning
confidence: 98%
“…It contains antioxidative properties which are mostly derived from phenolic contents [27]. Previously, cinnamon oil in combination with chitosan reduced decay percentage in sweet peppers [28], whereas combined application of cinnamon oil with gum arabic on papaya and banana fruit showed promising control of diseases like anthracnose [29]. Cinnamon oil incorporated with carnauba wax effectively controlled postharvest green and blue mold in citrus fruit [30], whereas cinnamon oil combined with chitosan coating preserved jujube fruit quality under low temperature storage [31].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, essential oils, antioxidants, organic and inorganic salts were used as fungicidal alternatives, that is, basil oil (Ocimum basilicum), cinnamon oil (Cinnamomum zeylanicum) and clove oil (Cymbopogon nardus). Low concentrations of essential oils were used against banana crown rot disease and their fungal pathogens; they were also used to maintain quality during storage (Ranasinghe et al, 2002;Anthony et al, 2003Anthony et al, , 2004Maqbool et al, 2010Maqbool et al, , 2011Abd-Alla et al, 2014). Salts, that is, potassium sorbate, calcium propionate, sodium bicarbonate, sodium carbonate, and ammonium bicarbonate reduced crown rot incidence of banana fruits (Dionisio and Kobayashi, 2004).…”
Section: Author(s) Agree That This Article Remains Permanently Open Amentioning
confidence: 99%
“…Anthony et al (2004) and Maqbool et al (2010) found that cinnamon oil suppressed mycelial growth and inhibited conidial germination (83.2%) of C. musae. Maqbool et al (2011) reported that lemon grass at 0.05 and 0.4% had fungicidal activity against C. musae and Colletotrichum gloeosporioides, the causal organisms of banana and papaya anthracnose diseases, respectively. Abd-Alla et al (2014) found that cinnamon, thyme oils completely inhibited 100% mycelium growth and conidial germination of F. semitectum, the cause of crown rot of banana fruits.…”
Section: Antifungal Activity Of Essential Oils Against Causal Organismsmentioning
confidence: 99%